Diel Patterns of Pheromone Release by Male Sea Lamprey. (3rd September 2021) - Fissette, Skye D; Bussy, Ugo; Huerta, Belinda; Brant, Cory O; Li, Ke; Johnson, Nicholas S; Li, Weiming
Abstract: Costs to producing sexual signals can create selective pressures on males to invest signaling effort in particular contexts. When the benefits of signaling vary consistently across time, males can optimize signal investment to specific temporal contexts using biological rhythms. Sea lamprey, Petromyzon marinus, have a semelparous life history, are primarily nocturnal, and rely on pheromone communication for reproduction; however, whether male investment in pheromone transport and release matches increases in spawning activity remains unknown. By measuring (1) 3keto-petromyzonol sulfate (3kPZS, a main pheromone component) and its biosynthetic precursor PZS in holding water and tissue samples at six points over the course of 24 hours and (2) 3kPZS release over the course of several days, we demonstrate that 3kPZS release exhibits a consistent diel pattern across several days with elevated pheromone release just prior to sunset and at night. Trends in hepatic concentrations and circulatory transport of PZS and 3kPZS were relatively consistent with patterns of 3kPZS release and suggest the possibility of direct upregulation in pheromone transport and release rather than observed release patterns being solely a byproduct of increased behavioral activity. Our results suggest males evolved a signaling strategy that synchronizes elevated pheromone release with nocturnal increases in sea lamprey behavior. This may be imperative to ensure that male signaling effort is not wasted in a species having a single, reproductive event.